Analyst Dividend Forecasts and Their Usefulness to Investors - Bilinski, Pawel; Bradshaw, Mark T. (The Accounting Review, 2022)
ABSTRACT In contrast to the disappearing dividends view prevalent in the literature, we document extensive dividend payments by firms and significant variability within firms and across 16 countries during 2000–2013. We predict that within-firm variability in dividends increases investor demand for forward-looking dividend information, and analysts respond by producing informative dividend forecasts. We find that analyst dividend forecasts are available for most dividend-paying firms and are more prevalent for firms with higher variability of dividends. Analyst dividend forecasts are more accurate than alternative proxies based on extrapolations of past dividends. Finally, dividend forecasts (1) are incrementally useful to investors beyond information in other fundamentals, such as earnings and cash flow forecasts, (2) help investors interpret earnings quality, and (3) are associated with investors' portfolio allocation decisions. Data Availability: Data are available from the public sources cited in the text.